Got religion? : how churches, mosques, and synagogues can bring young people back - Riley, Naomi Schaefer (Templeton Press, 2014)
Why are young people dropping out of religious institutions? Can anything be done to reverse the trend? In Got Religion?, Naomi Schaefer Riley examines the reasons for the defection, why we should care, and how some communities are successfully addressing the problem. The traditional markers of growing up are getting married and becoming financially independent. But young adults are delaying these milestones, sometimes for a full decade longer thantheir parents and grandparents. This new phase of "emerging adulthood" is diminishing the involvement of young people in religious institutions, sapp.